Re-thinking clinical research training in residency - O'Brien, Jennifer; D'Eon, Marcel (Revue canadienne de l'éducation médicale, 2014)
Background: There are good reasons to train clinician researchers, including a lack of translational and patient centered research, a decline in physicians choosing academic careers, the need for physicians who are able to critically appraise research, and accreditation requirements. However, why are we insisting that residents engage in original clinical research? Discussion: This paper is structured around three questions: 1) Is mandating original research the answer? 2) What ought to be the central purpose of research training? And 3) What are the alternatives to original clinical research? The successful development of clinician-scientists involves many more factors than resident research training. While invoking social accountability and public welfare, we argue for considering the opportunity cost of resident research training. We question the focus on original resident research and challenge medical educators to encourage research training aimed steadfastly at public good in the local setting. Finally, we offer preliminary suggestions for how to move forward. Conclusions: We conclude that medical educators should critically re-think our programs to develop resident researchers. If it is worthwhile to require original research projects during residency, then we must consider the priorities of local settings to best serve the public interest.